La Biennale di Venezia 1962 : XXXI Biennale Internazionale d'Arte - 31B. - Siciliano, Italo; Dell'Acqua, Gian Alberto; XXXI Biennale Internazionale d'Arte, Venezia, 1962 (Venezia : La Biennale di Venezia, 1962)
Abis, Mario ; Abreu, Mario ; Adams, Robert ; Ajmone, Giuseppe ; Andrich, Lucio ; Arikha, Avigdor ; Arp, Hans (Jean) ; Avramidis, Joannis ; Banchieri, Giuseppe ; Barbaro, Saverio ; Barbini, Alfredo ; Barisani, Renato ; Barovier & Toso ; Bartolini, Luigi ; Basso, Guido ; Bauch, Jan ; Bergner, Yosl ; Bergolli, Aldo ; Bernath, Aurel ; Berni, Antonio ; Bernik, Janez ; Boccioni, Umberto ; Bodini, Floriano ; Borsato, Renato ; Bottani, Grazia ; Braque, Georges ; Broggini, Luigi ; Bruscaglia, Renato ; Brzozowski, Tadeusz ; Cabrera, German ; Caille, Pierre ; Calder, Alexander ; Calo, Aldo ; Canogar, Rafael ; Capogrossi, Giuseppe ; Capralos, Christos ; Carmassi, Arturo ; Carpigiani, Dante ; Carrà, Carlo ; Carreno, Omar ; Casorati Pavarolo, Francesco ; Casorati, Felice ; Cassani, Nino ; Cassinari, Bruno ; Castello, Raffaele ; Cazzaniga, Giancarlo ; Cenedese, Gino ; Ceschia, Luciano ; Chadwick, Lynn ; Chauvin, Jean ; Chillida, Eduardo ; Chiti, Guido ; Ciarrocchi, Arnoldo ; Clark, Lygia ; Cocever, V.A. ; Comazzi, Luigi ; Consagra, Pietro ; Corneille ; Dalwood, Hubert ; Van Damme, Suzanne ; Davico, Mario ; Deluigi, Mario ; Derkert, Siri ; Dova, Gianni ; Dufy, Raoul ; De Echevarria, Federico ; Eibisch, Eugeniusz ; Ernst, Max ; Fasce, Gianfranco ; Fautrier, Jean ; Fazzini, Pericle ; Feigin, Dov ; Franco, Francesco ; Fulla, L'Udovit ; Gador, Istvan ; Gali, Zvi ; Garelli, Franco ; Gaspari, Luciano ; Gerstein, Noemi ; Giacometti, Alberto ; Gianquinto, Alberto ; Gilles, Werner ; Giordano, Edoardo ; Gliha, Oton ; Gorky, Arshile ; Grassman, Marcello ; Greco, Emilio ; Grieshaber, HAP ; Grosso, Luigi ; Guerrini, Lorenzo ; Guitet, James ; Hadzi, Dimitri ; Hartung, Hans ; Heerup, Henry ; Horno-Poplawski, Stanislaw ; Hundertwasser ; Jancic, Olga ; Kawabata, Minoru ; Konenkov, Sergej
Kurucz, Istvan D. ; Lavonen, Anti ; Licini, Osvaldo ; Loffredo, Silvio ; Lumenform ; MacIver, Loren ; Magnolato, Cesco ; Mairovich, Zvi ; Mandelli, Pompilio ; Manessier, Alfred ; Manfredi, Domenico ; Mannucci, Edgardo ; Marfaing, André ; Martina, Piero ; Martini, Alberto ; Martini, Arturo ; Martins, Aldemir ; Martyn, Ferenc ; Mascherini, Marcello ; Masereel, Frans ; Mastroianni, Umberto ; Mattioli, Carlo ; Meier-Denninghoff, Brigitte ; Messagier, Jean ; Mikenas, Juozas ; Milani, Umberto ; Minguzzi, Luciano ; Moilliet, Louis ; Moore, Henry ; Morandi, Giorgio ; Morandis, Gino ; Morlotti, Ennio ; Mukai, Ryokuchi ; Müller, Jan ; Music, Zoran ; Nesch, Rolf ; Nevelson, Louise ; Nolde, Emil ; Oveissi, Nasser ; Padoan, Giulio ; Parzini, Luigi ; Pedersen, Carl-Henning ; Perilli, Achille ; Pirandello, Fausto ; De Poli, Paolo ; Poliakoff, Serge ; Pomodoro, Gio ; Ramous, Carlo ; Redon, Odilon ; Reggiani, Mauro ; Richards, Ceri ; Riopelle, Jean Paul ; Romagnoni, Giuseppe ; Romani, Romolo ; Rosa, Andreina ; Rossi, Attilio ; Ruggeri, Pietro ; Rumohr, Knut ; Saetti, Bruno ; Salakhov, Tair ; Santomaso, Giuseppe ; Santoro, Pasquale ; Sarian, Martiros ; Saroni, Sergio ; Sbisa, Carlo e Mirella ; Scarpa, Romualdo ; Schilling, Albert ; Schumacher, Emil ; Scroppo, Filippo ; Serrano, Pablo ; Servranckx, Victor ; Sironi, Mario ; Sklenar, Zdenek ; Sommath, Hore ; Spacal, Luigi ; Speck, Paul ; Srbinovic, Mladen ; Stevo, Jean ; Strebelle, Olivier ; Suarez, Antonio ; Sugimata, Tadashi ; Szapocznikow, Alina ; Tajiri, Shinkichi ; Tapper, Kain ; Testa, Clorindo ; Tirronen, Esko ; Tobey, Mark ; Toso, Fratelli ; Tot, Amerigo ; Tura, Tulay ; Vecchiati, Pompeo ; Vedova, Emilio ; Vela, Vicente ; Venini Seguso Vetri d'Arte ; Ventayol, Juan ; Virduzzi, Antonino ; Volpi, Alfredo ; Wagemaker, Jaap ; Yeats, Jack Butler ; Zadkine, Ossip ; Zivr, Ladislav
XXXI Biennale Internazionale d'Arte, Venezia, 16 giugno - 07 ottobre 1962
Italiaans
boek